P365Protection against doxorubicine-induced cardiomyopathy by bergamot polyphenols through myocyte survival and cardiac stem cell activation. (15th July 2014) - Carresi, C; Aquila, I; Marino, F; Musolino, V; Correale, C; Gliozzi, M; Ellison, GM; Nadal-Ginard, B; Torella, D; Mollace, V
Abstract: Purpose: The clinical use of Doxorubicin (DOX) has the serious drawback of cardiotoxicity, which over time causes a cardiomyopathy leading to heart failure. The molecular pathogenesis of anthracycline cardiotoxicity remains highly controversial. Recently, it has been suggested that resident endogenous cardiac stem/progenitor cell (eCSC) depletion contributes to DOX-induced cardiomyopathy. Dietary polyphenols play a beneficial cardiovascular protecting role due to their pleiotropic anti-oxidative/inflammatory effects. Thus, we have investigated whether a mixture of flavonoids extracted from Bergamot (Citrus Bergamia, an endemic plant from Southern Italy), the bergamot-derived polyphenolic fraction (BPF), could attenuate myocyte damage and improve myocyte regeneration through eCSC activation in DOX-induced cardiomyopathy. Methods: We first assessed BPF's effects on DOX-induced damage in CSCs in vitro. For in vivo studies, Wistar male rats (n=36) were randomly assigned to receive intra-peritoneal injection of saline (that served as controls, CTRL, n=6), BPF (20mg/kg daily, n=10), DOX (6 doses of 2, 5mg/Kg from day 1 to day 14, n=10), and DOX+BPF (n=10). To track new cardiac cell formation all animals were implanted with subcutaneous micro-pumps to systemically release BrdU over 21 days when the rats were sacrificed. Results: BPF significantly reduces reactive oxygen species (ROS) accumulation and apoptotic death in CSCs in vitro. Intriguingly, BPF enhanced CSC specification into beating cardiomyocytes in vitro. Importantly, BPF in vivo treatment was able to prevent DOX-induced LV impairment. Echocardiography imaging demonstrated that DOX+BPF group had a significantly improved ejection fraction, fractional shortening and myocardial strain when compared to DOX-treated rats. DOX caused significant myocyte apoptosis with reactive myocyte hypertrophy when compared to CTRL. c-kit+ eCSC number was not significantly higher in DOX compared to CTRL. Only rare BrdU labelled cardiac cell nuclei but no BrdU+ myocytes were identified in DOX-induced cardiomyopathy, showing a lack of myocardial regeneration. On the contrary, BPF significantly reduced myocyte loss and myocyte hypertrophy by DOX. This improvement was associated with an increased number of activated BrdU+ eCSCs and differentiating newly-formed BrdU+ cardiomyocytes. Conclusions: BPF reduces DOX-induced cardiotoxicity decreasing myocyte loss and enhancing CSC activation and cardiomyocyte replacement. These data suggest that a BPF-supplemented diet could have beneficial effects in attenuating cardiotoxicity in patients requiring anthracycline chemiotherapy.